Hematological, oxidative stress, and immune status profiling in elite combat sport athletes - Dopsaj, V.; Martinovic, J.; Dopsaj, M.; Kasum, G.; Kotur-Stevuljevic, J.; Koropanovski, N. (The Journal of Strength and Conditioning Research, 2013)
The aim of this study was to profile hematological, oxidative stress, and immunological parameters in male athletes who practiced combat sports and to determine whether the type of combat sport influenced the measured parameters. Eighteen karate professionals, 15 wrestlers, and 14 kickboxers participated in the study. Hematological, iron-related, oxidative stress, and immunological parameters were measured at the beginning of a precompetitive period. The general linear model showed significant differences between the karate professionals, wrestlers, and kickboxers with respect to their hematological and iron status parameters (Wilks' Lambda = 0.270, F = 2.186, p < 0.05) and oxidative stress status (Wilks' Lambda = 0.529, F = 1.940, p < 0.05). The immature reticulocyte fraction was significantly higher in wrestlers (0.30 ± 0.03) compared with kickboxers (0.24 ± 0.04; p < 0.05) and karate professionals (0.26 ± 0.04; p < 0.05). Low hemoglobin density was significantly lower in wrestlers and kickboxers (p < 0.05) compared with karate professionals (karate: 3.51 ± 1.19, wrestlers: 1.95 ± 1.10, and kickboxers: 1.77 ± 0.76). Significant differences were observed between the karate professionals and wrestlers with respect to their pro-oxidant-antioxidant balance (437 ± 103 vs. 323 ± 148, p < 0.05) and superoxide-dismutase activity (SOD) (73 ± 37 vs. 103 ± 30, p < 0.05). All the measured parameters (with the exception of SOD activity) fell within their physiological ranges, indicating that the study participants represented a young and healthy male population. Hematological parameters differed between kickboxers and karate professionals. The low pro-oxidant-antioxidant balance and high SOD activity in wrestlers could be associated with the long-term impact of wrestling as a type of strenuous exercise